Urgensity of Environmental Management System Implementation on Oil Palm Plantation Management Policies in North Sumatera - Nasution, Ade Parlaungan; Wibowo, Edwin Agung; Ramdani, Ramdani; Rofiqah, Tamama (Journal of Social Transformation and Regional Development, 2021)
The development of oil palm plantations and its expansion as well, ensured potentially give impact on the environment. A standardized environmental management system is required by companies to develop and implement environmental aspects. This research is classified as a qualitative research with a case study which emphasizes potential environmental impacts analysis of oil palm plantations and the urgency of environmental management systems in oil palm plantation management policies in North Sumatra. The research results showed that there were potential environmental impacts began pre-construction, construction and operational stages related to oil palm plantations development such as erosion, changes of sustainable and quantity of water, plant pests distribution, diseases and weeds, changes in soil fertility, potential social conflicts and the emergence of the spread of plant diseases endemic and disruption of water infiltration function in peat areas. In addition, it affected environmental factors including ecosystem condition, hydrology, landscape, and resident’s attitude around the plantation. Alternative policies which be carried out related to environmental preservation and community welfare are (1) agro-industrial development policies that process oil and palm oil waste, (2) Moratorium (temporary suspension) of illegal logging, (3) Establish policy synergies and improve communication between government agencies and institutions, (4) reduce conflicts over land freehold by reforming above the law.